A novel and rapid microbiological assay for ciprofloxacin hydrochloride - Edith Cristina Laignier Cazedey; Hérida Regina Nunes Salgado (Elsevier, 2013)
The present work reports a simple, fast and sensitive microbiological assay applying the turbidimetric method for the determination of ciprofloxacin hydrochloride (CIPRO HCl) in ophthalmic solutions. The validation method yielded good results and included excellent linearity, precision, accuracy and specificity. The bioassay is based on the inhibitory effect of CIPRO HCl upon the strain of Staphylococcus epidermidis ATCC 12228 used as the test microorganism. The results were treated statistically by analysis of variance (ANOVA) and were found to be linear (r=0.9994, in the range of 14.0â56.0Â Âµg/mL), precise (intraday RSD%=2.06; interday RSD%=2.30) and accurate (recovery=99.71%). The turbidimetric assay was compared to the UV spectrophotometric and HPLC methods for the same drug. The turbidimetric bioassay described on this paper for determination of ciprofloxacin hydrochloride in ophthalmic solution is an alternative to the physicochemical methods disclosed in the literature and can be used in quality control routine. Keywords: Antibiotics, Fluoroquinolones, Ciprofloxacin hydrochloride, Quality control, Microbiological assay, Turbidimetric method